2020
DOI: 10.1002/dev.21998
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the acoustic features of social play‐induced 50‐kHz ultrasonic vocalizations: A detailed spectrographic analysis in wild‐type Sprague–Dawley and Cacna1c haploinsufficient rats

Abstract: Sexual dimorphisms are widespread in the animal kingdom. At the behavioral level, there is evidence for sex differences in social play behavior. In rats, males typically engage more in rough‐and‐tumble play than females. One prominent component of the rough‐and‐tumble play repertoire in rats is the emission of 50‐kHz ultrasonic vocalizations (USV). Such 50‐kHz USV reflect the rewarding nature of play and serve as socioaffective signals. Here, we provide evidence for sexual dimorphisms within rough‐and‐tumble p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Female rat USVs also had a higher peak frequency. For experimental animals, female rats produced a similar rate of 50 kHz USVs during play as male control animals, whereas experimental male animals had reduced 50 kHz USV production during play [115,116].…”
Section: Cacna1c P32-p34 Cacna1c 5 Minmentioning
confidence: 89%
“…Female rat USVs also had a higher peak frequency. For experimental animals, female rats produced a similar rate of 50 kHz USVs during play as male control animals, whereas experimental male animals had reduced 50 kHz USV production during play [115,116].…”
Section: Cacna1c P32-p34 Cacna1c 5 Minmentioning
confidence: 89%
“…Both studies used the same strain of rat, the same 2 min expectation window, and similar methods of food deprivation. Burgdorf et al did use a mix of male and female rats while we used solely males, but previous studies have shown that sex differences in vocalizations are either subtle or non-existent [ 45 , 46 , 47 ] (see below). Hence, the most notable difference was that we used juvenile rats while they, and all the other studies cited above, used adults.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, juvenile male rats play more than female rats [ 54 , 55 ]. It is hence not surprising that one recent study in Sprague-Dawley rats found lower overall vocalizations in juvenile females [ 47 ]. The authors also found decreases in specific calls (flat and step) but not others (trill).…”
Section: Discussionmentioning
confidence: 99%
“…Male offspring were housed in litter-mate pairs and allowed food and water ad libitum until reaching maturity (3 months of age). Although recent research indicates there is a sexually dimorphic expression of USVs in rats ( Kisko et al., 2021 ), only male rats were included in the present study. This was due to resource limitations, to align with previous research in our laboratory, and to limit variation in the data.…”
Section: Methodsmentioning
confidence: 99%